Interaction of soluble organic matter with metal oxides used as ceramic membrane for drinking water pretreatment - Dramas, L.; Croue, Jean-Philippe (2012)
Throughout the world, a trend to intensify use of desalination as a means to reduce current or future water scarcity is observed. Membrane desalination is an extremely good technique for the removal of colloids, dissolved organic matter and salts. However this technique is very sensitive to fouling. Therefore, it is important to control the fouling of the Reverse Osmosis membrane to insure a long lifetime of the membrane. Pretreatment is a good way to control the fouling. In this project, ceramic membrane ultrafiltration is considered as pretreatment before RO. Interactions between organic matter from different sources and ceramic membranes are studied to evaluate the efficiency of ceramic ultrafiltration as a pretreatment before RO. Terrestrial organic matter extracted from a treatment plant and marine organic matter from algae culture and sea are investigated. These organic materials show different organic content, hydrophobic character and molecular weight distribution (LC-OCD profiles). Filtration of marine organic matter leads to higher fouling than terrestrial organic matter (decline of 85% in the first ten minutes for Chlorella vulgaris exudates), for a smaller content of organic matter (DOC of marine solutions = 3 - 4 mg/L; DOC of brackish water = 10 mg/L). Analyses of backflush and chemical cleaning solutions show that Low Molecular Weight (LMW) compounds and High Molecular Weight (HMW) compounds are preferentially retained in the ceramic membrane. © 2012 American Water Works Association.